Exploring the Disproportionate Impact of COVID-19 in Older Adults in Canada - Mujabad Shah; Karan Gupta; Yamini Sharma; Vineeta Singh; Carla Emilia Ibarra; Kajan Kugathasan (University Library System, University of Pittsburgh, 2023)
Background - Why are older Adults are Higher Risk? • The majority of older adults have comorbid conditions, which are associated with a higher risk for COVID-19. • Many live in residential care homes, which have seen the highest number of covid-19 cases due to tightly shared living spaces. • With weakened immune systems, older adults living in poverty face additional challenges in protecting themselves from the virus, as it is difficult for them to comply with public health measures such as social distancing. • 5% of individuals in the lowest income quartile were hospitalized due to covid19, compared to only 11.4% of individuals from the highest income quartile.   Methods - The data was retrieved from the Canadian MIS Database (CMDB) and the discharge abstract database (DAD). The CMDB contains financial and statistical operations information on public hospitals and regional health authorities across Canada. Case selection is based on COVID-19 diagnosis codes available in the International Statistical Classification of Diseases and Related Health Problems.   Results - Elderly faced higher rates of hospitalization during the pandemic. The average length of hospital stay was also higher for older adults-hospitalizations of individuals under age 65 without comorbidity 41,707 with comorbidity 12,372. Hospitalizations of individuals 65 and older without comorbidity were 22,221 with comorbidity 24,731. Higher Hospitalization rates and issues of inequality in the healthcare system globally. As the pandemic progressed, hospitalization increased in number significantly. The average length of stay for individuals younger than age 65 without comorbidity is 7.7 days compared to 17.0 days in patients with comorbidity. The average full length of stay for individuals 65 and older without comorbidity was 13.2 days, While in patients with comorbidity 19.2 days. Older adults had higher in-facility death rates due to COVID-19 hospitalization. The in-facility death rate of individuals younger than 65 without comorbidity is 2.5%, With comorbidity at 12.9%. In-facility death rate of individuals 65 and older without comorbidity is 14.4%, with comorbidity at 23.2%.   Conclusion - By analyzing and comparing various hospitalization rates for Canada, the precise data indicate that older adults have been disproportionatelyimpacted by COVID-19. It is now important to determine the underlying structural issues that have caused this inequality to prioritize healthy aging.